2018
DOI: 10.1667/rr14928.1
|View full text |Cite
|
Sign up to set email alerts
|

Significant Suppression of CT Radiation-Induced DNA Damage in Normal Human Cells by the PrC-210 Radioprotector

Abstract: While computed tomography (CT) is now commonly used and considered to be clinically valuable, significant DNA double-strand breaks (γ-H2AX foci) in white blood cells from adult and pediatric CT patients have been frequently reported. In this study to determine whether γ-H2AX foci and X-ray-induced naked DNA damage are suppressed by administration of the PrC-210 radioprotector, human blood samples were irradiated in a CT scanner at 50-150 mGy with or without PrC-210, and γ-H2AX foci were scored. X-ray-induced n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In a recent head-to-head comparison of PrC-210 against 13 other commonly studied antioxidants and ROS scavengers, PrC-210 clearly demonstrated its superiority as a ROS scavenger. 17 N-acetylcysteine actually increased ROS-induced damage, and other molecules, including glutathione and vitamin E, were without effect or showed only a small effect over hours to days due to indirect mechanisms of action. One exception was WR-1065, the active form of amifostine, which though effective, is clinically precluded due to severe side effects.…”
Section: Discussionmentioning
confidence: 89%
“…In a recent head-to-head comparison of PrC-210 against 13 other commonly studied antioxidants and ROS scavengers, PrC-210 clearly demonstrated its superiority as a ROS scavenger. 17 N-acetylcysteine actually increased ROS-induced damage, and other molecules, including glutathione and vitamin E, were without effect or showed only a small effect over hours to days due to indirect mechanisms of action. One exception was WR-1065, the active form of amifostine, which though effective, is clinically precluded due to severe side effects.…”
Section: Discussionmentioning
confidence: 89%
“…The gel-based assay of ·OH-induced plasmid DNA breaks, in which a 90-second pulse of ·OH was generated by x -ray, demonstrated that PrC-210 provided 100% suppression of the ·OH insult that otherwise induced >95% damage to the naked plasmid DNA. 23 Because several of the comparison molecules absorb UV light, the H 2 O 2 + UV light ·OH generator used in an earlier report 24 was replaced here with 90-second x-irradiation to produce the ·OH insult. In a previous titration comparison of antioxidants, 23 6 mmol/L PrC-210 was found to confer complete protection (Figure 3 A), so the molecules were compared here by addition at 6 mmol/L to DNA 10 minutes before the 90 seconds ·OH insult (Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
“… 23 Because several of the comparison molecules absorb UV light, the H 2 O 2 + UV light ·OH generator used in an earlier report 24 was replaced here with 90-second x-irradiation to produce the ·OH insult. In a previous titration comparison of antioxidants, 23 6 mmol/L PrC-210 was found to confer complete protection (Figure 3 A), so the molecules were compared here by addition at 6 mmol/L to DNA 10 minutes before the 90 seconds ·OH insult (Figure 3 B). Under these comparison conditions, none of the current UW solution antioxidants (ie, glutathione, adenosine, and allopurinol) 28 or proposed antioxidants in the new BUPS Solution 28 (ie, taurine, N-acetylcysteine, and ascorbic acid) showed any protection, while PrC-210 showed 100% protection of the at-risk plasmid DNA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations